2011
DOI: 10.1097/sla.0b013e3182171c48
|View full text |Cite
|
Sign up to set email alerts
|

Total or Posterior Partial Fundoplication in the Treatment of GERD

Abstract: Both a total and a partial posterior fundoplication maintain a high level of reflux control after 2 decades of follow up. The previously reported differences in mechanical side effects, in favor of the partial wrap, seemed to disappear over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 23 publications
6
18
0
Order By: Relevance
“…Nevertheless, no trials have demonstrated a significant reduction in postoperative dysphagia rate or provided clear evidence to support routine application of LTF. [ 12 14 ] Memon et al [ 36 ] conducted a meta-analysis comparing laparoscopic anterior with posterior fundoplication, and the results of the study suggested laparoscopic anterior fundoplication was a better alternative to laparoscopic posterior fundoplication. However, it is not appropriate to generalize 2 types of partial fundoplication into 1 category and it would reduce the credibility of the results of the meta-analysis above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, no trials have demonstrated a significant reduction in postoperative dysphagia rate or provided clear evidence to support routine application of LTF. [ 12 14 ] Memon et al [ 36 ] conducted a meta-analysis comparing laparoscopic anterior with posterior fundoplication, and the results of the study suggested laparoscopic anterior fundoplication was a better alternative to laparoscopic posterior fundoplication. However, it is not appropriate to generalize 2 types of partial fundoplication into 1 category and it would reduce the credibility of the results of the meta-analysis above.…”
Section: Discussionmentioning
confidence: 99%
“…Constructing a posterior partial fundoplication is an alternative approach. The outcomes of RCTs [ 12 , 13 ] and a meta-analysis [ 14 ] we conducted previously have not shown a significant reduction in postoperative dysphagia following posterior partial fundoplication and “tailored therapy” has not been supported based on preoperative esophageal motility.…”
Section: Introductionmentioning
confidence: 99%
“…However, subgroup analyses suggested that differences in the prevalence of dysphagia between two techniques disappeared over time. Furthermore, two decades follow-up results of a RCT [ 38 ] comparing open Nissen and Toupet demonstrated no difference in the prevalence of postoperative complications. As a reasonable and accurate index for assessing the efficacy of surgical treatment for GERD [ 39 , 40 ], the patient satisfaction was high (≈90 %) and comparable between the two arms.…”
Section: Discussionmentioning
confidence: 99%
“…T he risk of developing gastroesophageal reflux disease (GERD) increases with the severity of the anatomical changes and dysfunctions of the barrier against reflux of gastric contents through the esophagogastric junction (EGJ). [1][2][3] One therapeutic option for patients with GERD is daily intake of proton pump inhibitors (PPIs) to control symptoms and prevent the esophageal mucosa from reflux-induced damage. As an alternative, there is one well-established therapeutic option, ie, laparoscopic antireflux surgery.…”
mentioning
confidence: 99%